Therapeutic properties of oyster mushroom (P. ostreatus) cultivation on different cellulosic substrates - Akyuz, Mehmet; Inci, Sule; Kirbag, Sevda (Marmara Univ, 2023)
: The objectives of this work were to evaluate the antimicrobial activities, antioxidant in vitro cytotoxicity and DNA damage of Pleurotus ostreatus (Jacq.) P. Kumm. cultivation on some local cellulosic substrates. It observed to be very active against bacteria (except S. mutans and K. pneumonia), yeast and dermatophytes when compared to the control groups (10.0-32.7 mm). It also showed significant antioxidant potential, the highest TAS (0.978 mmol/L) and TOS (10.51 mu mol/L) values were obtained in M-P (1:1) and W, and also DPPH radical scavenging effects was more effective at 25 mg (74.80%) on MS. The methanol extract of P. ostreatus cultured on M-W (2.35%) and M-P (1:1) (9.74%) at 400 mu g/mL concentration has remarkably decreased the percentage of viability in MDA-MB-231 and A-549 cell lines. However, it has been determined that P. ostreatus does not have a DNA protective effect. These results indicate that P. ostreatus has potent antimicrobial, antioxidant, as well as cytotoxic effects.
Keywords: P; ostreatus; edible mushroom; medicinal effect; cytotoxicity; DNA damage